The Son of Man and the Sea Hydromachy and Conquest in Mark’s Sea Voyages - Vette, Nathanael 1990- (2025)
This study proposes a new reading of Jesus’ confrontations with the elemental and the demonic on the sea of Galilee – the stilling of the storm (Mk 4.35–41), the Gerasene demoniac (5.1–20) and Jesus walking on water (6.45–52) – in light of literary and material records associating hydromachy (battles against sea and river gods) with the conquest of land. Taken together these episodes reveal a Galilean Messiah who by subduing demonic waters is able to go on and conquer territory long held to be part of Israel, thereby fulfilling well-documented hopes for the restoration of the land and becoming the Jewish (as opposed to Roman) ‘lord of land and sea’.
Keywords: river gods; Josephus; Arch of Titus; Numismatics; early Roman empire; Rabbinic Literature; Gospel of Mark